Epicureanism - O'Keefe, Tim, 1968- (Acumen, 2010)
The Epicurean school of philosophy was one of the dominant philosophies of the Hellenistic period. Founded by Epicurus of Samos (century 341-270 BCE) it was characterized by an empiricist epistemology and a hedonistic ethics. This new introduction to Epicurus offers readers clear exposition of the central tenets of Epicurus' philosophy, with particular stress placed on those features that have enduring philosophical interest and where parallels can be drawn with debates in contemporary analytic philosophy. Part 1 of the book examines the fundamentals of Epicurus' metaphysics, including atoms a.
Keywords: Epicureans (Greek philosophy); Épicuriens.; PHILOSOPHY -- History & Surveys -- Ancient & Classical.; Epikureismus